TRENDS, POTENTIAL AND CHALLENGES OF HLI’s LEADERSHIP DURING COVID-19 PANDEMIC - Romzi Ationg,; Mohd Sohaimi Esa,; Mohd Azri Ibrahim,; Mohd Kamal Mohd Shah,; Muhammad Safuan Yusoff,; Irma Wani Othman,; Saifulazry Mokhtar, (Journal of Islamic, Social, Economics and Development, 2021)
The outbreak COVID-19 pandemic plays a significant impact on the functional ofHigher Learning Institutions (HLIs) globally. This is especially true in the area of leadership.But what exactly are the impacts of Covid-19 pandemic on HLI’s leadership? To understandthe impacts of Covid-19 pandemic on HLI’s leadership, exploring the trends, potentials andthe challenges associated with the issue is immensely valuable. Accordingly, by applying aqualitative approach through the examination of information gathered from various sourcessuch as books, journals and media reports, the paper presents a discussion on trends,potential and challenges of Higher Learning Institution’s (HLI) Leadership during Covid-19pandemic. The paper is expected to contribute in the understanding of trends, potential andchallenges of Higher Learning Institution’s (HLIs) Leadership during Covid-19 pandemic,thus led to the improvement of HLI’s leadership despite the pandemic.